Acute left pyelonephritis in patient with bilateral low back pain and ureteral duplicity: Case Report : Pielonefritis aguda izquierda en paciente con lumbalgia bilateral y duplicidad ureteral: Caso Clínico - Flores Sáenz, Manuel (2024)
The case presents a 46-year-old woman with left acute pyelonephritis and bilateral duplicated ureters. Acute pyelonephritis is a severe urinary tract infection that can vary in clinical presentation, from mild symptoms to sepsis. Lower back pain is a common symptom and can be unilateral or bilateral. Duplicated ureters are a congenital anomaly resulting in the transport of urine from the same kidney to the bladder, and can cause complications such as vesicoureteral reflux and ureteral obstruction. Treatment involved antibiotics and outpatient urology follow-up. The case underscores the importance of a meticulous diagnostic approach and consideration of underlying congenital anomalies that can complicate clinical management and treatment. The integration of clinical findings and complementary tests was essential for an accurate diagnosis and appropriate treatment plan.